Transcranial direct current stimulation: five important issues we aren't discussing (but probably should be) - Horvath, Jared C.; Carter, Olivia; Forte, Jason D. (Frontiers in Systems Neuroscience, 2014)
Transcranial Direct Current Stimulation (tDCS) is a neuromodulatory device often publicized for its ability to enhance cognitive and behavioral performance. These enhancement claims, however, are predicated upon electrophysiological evidence and descriptions which are far from conclusive. In fact, a review of the literature reveals a number of important experimental and technical issues inherent with this device that are simply not being discussed in any meaningful manner. In this paper, we will consider five of these topics. The first, inter-subject variability, explores the extensive between- and within-group differences found within the tDCS literature and highlights the need to properly examine stimulatory response at the individual level. The second, intra-subject reliability, reviews the lack of data concerning tDCS response reliability over time and emphasizes the importance of this knowledge for appropriate stimulatory application. The third, sham stimulation and blinding, draws attention to the importance (yet relative lack) of proper control and blinding practices in the tDCS literature. The fourth, motor and cognitive interference, highlights the often overlooked body of research that suggests typical behaviors and cognitions undertaken during or following tDCS can impair or abolish the effects of stimulation. Finally, the fifth, electric current influences, underscores several largely ignored variables (such as hair thickness and electrode attachments methods) influential to tDCS electric current density and flow. Through this paper, we hope to increase awareness and start an ongoing dialogue of these important issues which speak to the efficacy, reliability, and mechanistic foundations of tDCS.